Cochlear implantation for single-sided deafness after COVID-19 hospitalization. (2nd November 2021) - Asfour, Leena; Kay-Rivest, Emily; Roland, J. Thomas
Abstract : Introduction: Understanding the clinical manifestations of the coronavirus disease (COVID-19) has become an urgent objective in the research community. Amongst the emerging neurologic complications is sensorineural hearing loss. While several cases of hearing loss amongst COVID-19 patients have been reported, the management of these patients has yet to be discussed and determined. Herein we present cochlear implant outcomes for a patient who suffered from unilateral sensorineural hearing loss after a prolonged hospital course for COVID-19. Methods: A patient who was hospitalized for COVID-19 for one month and subsequently developed unilateral profound sensorineural hearing loss underwent cochlear implantation for single-sided deafness. His COVID-19 hospital course was reviewed in detail. Speech perception and audiometric assessments were used to evaluate cochlear implant outcomes. Results: After cochlear implantation, the patient demonstrated improved speech perception on the implanted side and decreased tinnitus within 1 month of activation. Conclusions: Cochlear implantation may be an appropriate intervention for patients who suffer from severe sensorineural hearing loss following infection with COVID-19.